A Case study: The enhancement of association football officiating through the application of performance psychology - Dougan, K.; Russell, P. (BASES Conference 2024, 2024)
Despite the growing professionalisation of sports, research on the performance psychology of match officials remains limited. For example, only 3% of sports psychology studies delve into referees and match officials (Hancock, Dawson, Auger, 2020, Journal of Sport Psychology, 12, 123-135). The Professional Game Match Officials Limited (PGMOL) has identified nine Key Performance Characteristics (KPCs) essential for measuring the performance and development of match officials. Among these, four align with performance psychology: developmental mindset, resilience, interpersonal skills, and leadership. With institutional ethical approval, this case study focuses on a 30-year-old male referee who has been officiating in the English Football League (EFL) for two years. Referred by his coach to enhance his interpersonal skills and emotional regulation, this intervention aimed to bolster these critical areas using a structured psychological approach based on Keegan`s model of applied sport psychology consultancy (Keegan, 2015, Journal of Science and Medicine in Sport, 19, 493). This six-week intervention included three meetings and attendance at one of the referee`s matches. The initial assess ment noted a strong technical knowledge but highlighted challenges in on field interpersonal interactions, resulting in ineffective communication and rapport building with players. Emotional responses sometimes compromised authority and decision-making. Interventions aimed to improve communi cation, conflict resolution, and emotional regulation during high-pressure scenarios. These interventions focused on analysing past incidents, identifying breakdown points, and formulating strategies for more effective handling of similar situations. Emotional regulation during high-pressure scenar ios, such as when issuing cards or managing mass confronta tions focused on slowing down processes and taking mindful breaths. Throughout the intervention, the match official actively engaged in reflective practice, supplemented using video clips to demonstrate his progress. These clips formed an integral part of the consultancy process, providing tangi ble evidence of improvement and facilitating targeted feed back. In and post intervention evaluation centered around behavioural changes, match official self-reflection and coach feedback. Results showed significant positive shifts in all areas, with increased acceptance and respect from teams, enhanced confidence, reduced conflict, improved emotional management, and authority maintenance. Observations high lighted the referee`s enhanced confidence and reduced con flict in interpersonal interactions, while feedback from the coach emphasised improvements in emotional management and authority maintenance. This case study demonstrates the efficacy of tailored psychological interventions in enhancing the interpersonal skills and emotional regulation of associa tion football match officials. Further research is recom mended to explore the enduring effects of such interventions and the applicability of KPCs across officiating levels.